Fatuamide A, a Hybrid PKS/NRPS Metallophore from a Leptolyngbya sp. Marine Cyanobacterium Collected in American Samoa - Alexander, Kelsey L.; Naman, C. Benjamin; Iwasaki, Arihiro; Mangoni, Alfonso; Leao, Tiago [UNESP]; Reher, Raphael; Petras, Daniel; Kim, Hyunwoo; Ternon, Eva; Caro-Diaz, Eduardo J. E.; Glukhov, Evgenia; Mitrevska, Jana A.; et al. (American Chemical Society (ACS), 2025)
A structurally novel metabolite, fatuamide A (1), was discovered from a laboratory cultured strain of the marine cyanobacterium Leptolyngbya sp., collected from Faga’itua Bay, American Samoa. A bioassay-guided approach using NCI-H460 human lung cancer cells directed the isolation of fatuamide A, which was obtained from the most cytotoxic fraction. The planar structure of fatuamide A was elucidated by integrated NMR and MS/MS analysis, and a combination of bioinformatic and computational approaches was used to deduce the absolute configuration at its eight stereocenters. A putative hybrid PKS/NRPS biosynthetic gene cluster responsible for fatuamide A production was identified from the sequenced genomic DNA of the cultured cyanobacterium. The biosynthetic gene cluster possessed elements that suggested fatuamide A binds metals, and this metallophore property was demonstrated by native metabolomics and indicated a preference for binding copper. The producing strain was found to be highly resistant to toxicity from elevated copper concentrations in culture media.